EVALUATION OF TRAINING FOR CONTRACEPTION SERVICES TRAINER FOR DOCTORS AND MIDWIFES IN HEALTH FACILITIESThe training for trainers on contraceptive services for doctors and midwives at Health Facilities was carried out for 14 days, using the blended learnin - Yunida, Helvy; Siswanto, Eddy (International Journal of Social Science, 2022)
The training for trainers on contraceptive services for doctors and midwives at Health Facilities was carried out for 14 days, using the blended learning method. Starting with the online method for 9 days, using zoom. Starting from July 4 to July 14, 2022. Participants complete their assignments and then upload them on Google Drive. Then the offline meeting which took place at the Sardjito Hospital Yogyakarta. It was held for 5 days on August 1-5 2022. The training participants consisted of 17 people, 5 people from West Java, 5 people from Papua, 5 people from West Papua and 2 people from Sardjito Hospital. Educational background of the participants who specialize in midwifery from the Indonesian Association of Genecology Organizations (POGI) and midwives from the Indonesian Midwives Association (IBI). Organization The learning method uses question and answer lectures, discussions, and simulations carried out in class, where participants are divided into 3 groups. The first group was West Java plus 1 person from Sardjito, group 2 from Papua 5 people plus 1 from Sardjito Hospital and group 3 consisted of 5 people from West Papua. Participants put the contraceptive IUD, implant, new method of condom on the mannequin. Furthermore, the practice of installing contraceptives at the Sardjito Hospital.